Axiological Review on The Source of Knowledge for Students at Madrasah Ibtidaiyah Yasua Pilangwetan - Ni’amah, Maysurin (International Tatho Academics, 2024)
This research aims to identify the foundation of truth as a source of knowledge for students in Madrasah Ibtidaiyah Yasua Pilangwetan from an axiological perspective. This research is a case study using a qualitative approach. Data collection techniques through data triangulation techniques. Data analysis through reduction, presentation, and verification techniques. The results showed that Madrasah Ibtidaiyah Yasua Pilangwetan has designed a curriculum and implemented teaching methods that reflect the values of truth. Teachers act as behavioral models, guides, and mentors, helping students to understand, appreciate, and apply truth values in their daily lives. The process of internalizing such truth values also affects students' moral and intellectual development, helping them to become responsible, moral, and critical-thinking individuals. Meanwhile, the challenges in integrating truth values require a holistic and sustainable approach, and collaboration between the school environment and the community plays an important role in supporting the cultivation of truth values to Madrasah Ibtidaiyah Yasua Pilangwetan learners. This research contributes to the understanding of Islamic education practices and their implications for the character building of learners in Madrasah.